Poor reactivity of posterior electroencephalographic alpha rhythms during the eyes open condition in patients with dementia due to Parkinson's disease - Babiloni, Claudio; Noce, Giuseppe; Tucci, Federico; Jakhar, Dharmendra; Ferri, Raffaele; Panerai, Simonetta; Catania, Valentina; Soricelli, Andrea; del Percio, Claudio (Elsevier Inc., 2024)
Here, we hypothesized that the reactivity of posterior resting-state electroencephalographic (rsEEG) alpha rhythms during the transition from eyes-closed to -open condition might be lower in patients with Parkinson's disease dementia (PDD) than in patients with Alzheimer's disease dementia (ADD). A Eurasian database provided clinical-demographic-rsEEG datasets in 73 PDD patients, 35 ADD patients, and 25 matched cognitively unimpaired (Healthy) persons. The eLORETA freeware was used to estimate cortical rsEEG sources. Results showed substantial (greater than ?10%) reduction (reactivity) in the posterior alpha source activities from the eyes-closed to the eyes-open condition in 88% of the Healthy seniors, 57% of the ADD patients, and only 35% of the PDD patients. In these alpha-reactive participants, there was lower reactivity in the parietal alpha source activities in the PDD group than in the healthy control seniors and the ADD patients. These results suggest that PDD patients show poor reactivity of mechanisms desynchronizing posterior rsEEG alpha rhythms in response to visual inputs. That neurophysiological biomarker may provide an endpoint for (non) pharmacological interventions for improving vigilance regulation in those patients.
Keywords: Alzheimer's Disease Dementia (ADD); Desynchronization of Alpha Rhythms; Exact Low-Resolution Brain Electromagnetic Source Tomography (eLORETA); Eyes Closed; Parkinson's Disease Dementia (PDD); Resting-State Electroencephalographic (EEG) Rhythms; Resting-State Eyes Open